Model Evaluasi Pasca Pelatihan Pejabat Inti Satuan Kerja Bidang Jalan dan Jembatan di Balai Diklat Wilayah IV Kementerian PUPR - Maria Iflah; Sedarmayanti Sedarmayanti; Teni Listiani (Jurnal Media Administrasi Terapan, 2022)
The Ministry of Public Works and Public Housing (PUPR) of the Republic of Indonesia is the leading sector in infrastructure development. To support this, PUPR for Roads and Bridges at the Regional IV Training and Education Center held training and conducted post-training evaluations for Core Work Unit Officials (PISK). Some of the problems faced, the evaluation of the training participants was considered to be still not optimal, because they had not been able to provide information about the outcomes of the training implementation. Another problem is the change in the quality of work of the alumni of the training participants has not provided a significant improvement for the organization. This study aims to analyze how the implementation of the post-training PISK evaluation is carried out, as well as to design an evaluation model. The method used in this research is a qualitative method, to elaborate a case more deeply and comprehensively. The results of the study indicate that the implementation of the current PISK training evaluation is carried out through pre-test and post-test. Referring to the Kirkpatrick model, the stages that have been carried out in the evaluation of employees who have attended training, are only at level 1 (reaction) and level 2 (learning), while posttraining levels 3 and level 4 have not been implemented. The results of further research indicate that in the implementation of the evaluation, the implementation of the results of the implementation of the training has not been able to accurately measure the success of the implementation of the training. To improve the process of evaluating the implementation of the training, a post-training evaluation model was designed that focuses more on aspects of assessment time, assessment standards or norms, assessment instruments and assessors.